Farmers Experiences on Evaluation Bt Cotton in Tamil Nadu - S. Usha Rani, G. Selvaraj (Indian Journal of Extension Education, 2022)
Bt cotton is an attractive alternative technology to protect cotton from bollworms and to make cotton farming more sustainable, economical and eco-friendly. It has the inbuilt resistance to bolloworms and is very effective in controlling the yield losses caused by bolloworms to a considerable extent. It results in improvement of yield levels and also improves margin of profit to the farmers. Though the technology crowns the credits of various benefits, it’s end users have certain concerns about it’s bio-safety, ethical, social, health, economic and environmental implications. These concerns prophesize that there will be resistance against GE crops in general and Bt cotton in particular in near future. The attitude of the people, their awareness about the technology and their adoption behaviour play a major role in sustaining any technology. Keeping this in mind, an empirical study was conducted among 120 randomly selected Bt cotton growers at Coimbatore and Perambalur districts of Tamil Nadu to evaluate the experiences they had in Bt cotton cultivation. Majority of the growers had favourable attitude towards cultivation of Bt cotton and would like to grow Bt cotton in future too. Their primary sources of information about Bt cotton were the local input dealers. Majority of them had not adopted the refugee technology prescribed by the Government of India to avoid the development of resistance by bollworms to Bt cotton. They perceived that major social, economic, environmental, ethical and bio-safety implications would occur in near future due to intensive of Bt cotton.